Redesain tempat masak ergonomis warga lanjut usia dengan metode partisipatori - Purwanto, Purwanto (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Elderly residents who live in lansia X homes use the kitchen as a kitchen places for cooking activities, and have complaints about height and slippery floor conditions, according to the elderly as many as 32% of cooking kitchen users representing the elderly population using purposive sampling, proposed design improvements for elderly cooking places taking into account the anthropometric size of elderly users, using a focus group approach discussion to facilitate the wishes and complaints experienced by the elderly, the shape and size of the proposed new design for the elderly kitchen by adding a foothold in front of the kitchen to facilitate cooking reach, with the width of the kitchen: 53 cm; Height: 132cm; length 53 cm, using anthropometric measurements, namely front arm reach (JTD) 53 cm; shoulder width(LB) (maximum) 43 cm; height (TB) 158 cm; elbow height (TS) 132 cm. The design is the result obtained from the first FGD, then the results of the second FGD explain the proposed new design of an elderly kitchen for elderly residents, by having a height, width, length according to body size by adding non-permanent footing facilities in front making it easier for users to reach the kitchen for activities cooking, floors that are designed to be safe and non-slippery, and additional cupboard facilities to make it easier to store cooking utensils, the results of the different test show a significant difference Sig (2-tailed) of 0.003 <0.05 indicating that the H1 hypothesis is accepted.